Variação sazonal do zooplâncton nos estuários dos Rios Botafogo e Siriji, litoral Norte de Pernambuco – Brasil - LUCAS, Ana Paula Oliveira (2006)
The present work aimed at characterizing the seasonal variation of the zooplankton in the estuaries of the Botafogo and Siriji rivers, northern coast of Pernambuco. The collections were accomplished respectively in May/December 2004, months that included within rainy and dry seasons. Zooplankton samples were collected with net of 300 Qm and 68 Qm mesh size nets, coupled with a flowmeter, to measure the amount of filtered water. In the estuary of the Siriji river, the haulings were accomplished at the surface and above the bottom. Average density logaritmized values in the rainy season varied from 8.24 to 9.35 ind.m-3 in the surface, and 8.71 to 9.47 ind.m-3 at the bottom. In the dry season, these values floated between 7.90 and 9.44 ind.m-3 at the surface, and 4.16 to 9.72 ind.m-3 at the bottom. In the estuary of the Botafogo river, average densities in the rainy season varied from 7.32 to 8.86 ind.m-3 for the macrozooplankton (300 Qm) and, 3.35 to 12.59 ind.m-3 for the microzooplankton (68 Qm). In the dry season, these values floated of 6.14 and 8.40 ind.m-3 for the macrozooplankton and 3.35 to 9.43 ind.m-3 for the microzooplankton. Microzooplankton densities were, most of the time, superior to macrozooplâncton ones, indicating a greater contribution of small individuals (Copepoda nauplii, copepodits and adult). The association analysis showed a total separation of samples collected with different nets (300 and 68 Qm). The most outstanding organisms in the two studied estuaries were Oikopleura dioica, Oikopleura spp., Acartia lilljeborgi, Grapsidae/Ocypodidae/Majidae (zoeae I), Pseudodiaptomus acutus, Oithona oswaldocruzi, Oithona spp. and Copepoda nauplii. Both estuaries presented low species diversity and evenness, thus suggesting signs of environmental disturbances on the structure of the zooplankton community.